Analisis Kontribusi Dana Bagi Hasil (DBH) PT BP Tangguh LNG Terhadap Pendapatan Daerah Kabupaten Teluk Bintuni Tahun 2019-2023 - Tewernusa, Ketysia I (Lensa Ekonomi, 2024)
This study aims to analyze the contribution of the Revenue Sharing Fund (DBH) received from PT BP Tangguh LNG to the regional revenue of Teluk Bintuni Regency during the period of 2019–2023.The Revenue Sharing Fund (DBH) is one of the main sources of regional income derived from the natural resource sector, particularly oil and gas, and is expected to enhance the fiscal capacity and financial independence of the region. This study employs a descriptive quantitative method using a percentage analysis approach to measure the contribution of DBH to the total Local Own-Source Revenue (PAD) and overall regional revenue. The data used are secondary data obtained from the realization reports of the Teluk Bintuni Regency Regional Budget (APBD), as well as official financial reports and publications from the local government and related institutions. The results of the study indicate that the contribution of DBH from PT BP Tangguh LNG to regional revenue tends to fluctuate from year to year, yet it accounts for a significant proportion of the total regional income. This contribution reflects the strategic role of the oil and gas sector in supporting regional development, although there is still a high dependency on revenue from DBH.